A thermal analysis of the horizontal zone refining of indium antimonide - Roussopoulos, G. S.; Rubini, Philip A. (Elsevier, 2004)
Single crystals of semiconductors and optical materials are very important in the field of computer technology and communications. The properties of such crystalline materials significantly depend upon the quantity and the type of impurities contained in their structure. The principal objective of this work was to further the understanding of the heat transfer mechanisms in the horizontal zone refining process and, by successfully modelling the process, to obtain a correlation between the length of the molten zone and typical operational parameters, for example, the physical dimensions of the process equipment, the heating element and the required energy input. Results are presented from the associated parametric study accomplished through a three-dimensional pseudo-steady-state simulation of the zone refining process for indium antimonide. The conclusions will be of value when optimizing the operating efficiency of horizontal zone refining where the length of the molten zone is a significant factor.
Keywords: Convection; Zone melting and refining; Computer simulation; Heat transfer; Conduction